Association of ZFHX3 gene variation with atrial fibrillation, cerebral infarction, and lung thromboembolism: An autopsy study. Issue 2 (August 2017) - Zaw, Khin Thet Thet; Sato, Noriko; Ikeda, Shinobu; Thu, Kaung Si; Mieno, Makiko Naka; Arai, Tomio; Mori, Seijiro; Furukawa, Tetsushi; Sasano, Tetsuo; Sawabe, Motoji; Tanaka, Masashi; Muramatsu, Masaaki
Abstract: Aim: We aimed to study a single nucleotide polymorphism (SNP), rs2106261, in the transcription factor gene, ZFHX3, in atrial fibrillation (AF) and other related phenotypes by phenome scanning in a Japanese population. Method: We retrieved consecutive autopsy data ( n  = 2433, mean age = 80 years) from the Japanese SNP database for geriatric diseases (JG-SNP). Clinical data, including an AF diagnosis, were collected from medical charts. Genotyping was performed with the DNA chip method. We also analyzed 42 pathological and 26 clinical phenotypes, including cerebral infarctions (CIs) and lung thromboembolisms (LTs), diagnosed by macroscopic inspection during the autopsy. Result: Among the 2433 patients with available data, 18.6% had AF, 29.4% had CI, and 4.9% had LT phenotypes. The A allele of the rs2106261 SNP was significantly associated with AF, after adjusting for age, sex, diabetes, hypertension, and smoking (AA + AG/GG, OR = 1.51, 95%CI: 1.16–1.97, p  = 0.002). In the entire cohort, CI was not associated with rs2106261 ( p  = 0.14). However, among patients under 80 years old, rs2106261 was significantly associated with CI (AA + AG/GG, OR = 1.57, 95%CI: 1.09–2.26, p  = 0.01). LT was also associated with rs2106261 (AA + AG/GG, OR = 1.99, 95%CI: 1.31–3.01, p  = 0.001). Associations between rs2106261 and CI and LT remained positive after adjusting for the presence of AF, which indicated that this SNP variant might serve as an independent risk marker. Conclusion: We showed that the ZFHX3 polymorphism, rs2106261 (A allele), was a risk marker for AF and AF-related phenotypes. The roles of this variant in the development of AF and its related phenotypes warrant further investigation.